2016 3rd International Conference on Electrical Engineering and Information Communication Technology (ICEEICT) 2016
DOI: 10.1109/ceeict.2016.7873115
|View full text |Cite
|
Sign up to set email alerts
|

A novel modified SFTA approach for feature extraction

Abstract: To increase the efficiency of conventional Segmentation Based Fractal Texture Analysis (SFTA), we propose a new approach on SFTA algorithm. We use an optimum multilevel thresholding hybrid method of Genetic Algorithm (GA) and Particle Swarm Optimization (PSO), called HGAPSO with the optimization technique for classification based on grey level range to get more accurate output. Experimental results show that proposed approach exhibits average 2% higher classification accuracy than conventional SFTA for our tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The dataset used here contains two datasets: 138 X-ray images, including 58 TB infected cases, and 662 X-ray images from Shenzhen Hospital with 336 TB cases. Several studies reported the application of artificial intelligence and DL for the case of healthcare, including COVID-19 [27][28][29][30][31][32][33][34][35][36][37][38]. One interesting study compared a multilayer network technique with a single network for the case of COVID-19 vaccinations; however, they did not consider disease diagnosis [35].…”
Section: Related Workmentioning
confidence: 99%
“…The dataset used here contains two datasets: 138 X-ray images, including 58 TB infected cases, and 662 X-ray images from Shenzhen Hospital with 336 TB cases. Several studies reported the application of artificial intelligence and DL for the case of healthcare, including COVID-19 [27][28][29][30][31][32][33][34][35][36][37][38]. One interesting study compared a multilayer network technique with a single network for the case of COVID-19 vaccinations; however, they did not consider disease diagnosis [35].…”
Section: Related Workmentioning
confidence: 99%
“…Accuracy is the percentage of correctly classified instances, or in other words, the ratio of the true results to the total number of cases examined [42,43]. This factor cannot differentiate between FN and FP error and considers them the same.…”
Section: -1-accuracymentioning
confidence: 99%
“…Using features that do not have much impact on finding the proper time history trend of crack occurrence can not only increase the computational complexity but can also introduce a fallacious trend, resulting in unintended and untimely alarms. Therefore, we need a feature selection algorithm to serve our purpose [37]. We incorporated the Boruta feature selector algorithm to sort out the useful features for calculating MDs.…”
Section: Boruta-mahalanobis Systemmentioning
confidence: 99%